Sleep quality, insomnia, chronic fatigue, and work performance in three-shift and fixed-night-shift nurses: a comparative cross-sectional study - Ji Eun Lee; Dong Yeon Kim; Hye Hyeon Shin; Su Hyeon Kim; Hee Young Choi (Journal of Korean Biological Nursing Science, 2026)
Purpose: This study compared sleep quality, insomnia, chronic fatigue, and work performance between nurses working fixed night shifts and those working rotating three-shift schedules and examined the relationships among these variables by work schedule type. Factors associated with work performance were also identified.Methods: This cross-sectional survey included nurses working at a university hospital. Data were collected using structured questionnaires measuring sleep quality, assessed with the Korean version of the Pittsburgh Sleep Quality Index, insomnia, chronic fatigue, and work performance. Data were analyzed using descriptive statistics, nonparametric tests, Spearman’s correlation coefficients, and hierarchical multiple regression analysis using SPSS version 30.0 program.Results: Insomnia differed significantly between nurses working fixed night shifts and those working rotating three-shift schedules. Among nurses on rotating three-shift schedules, poorer sleep quality, greater insomnia, and higher chronic fatigue were significantly associated with lower work performance, whereas sleep-related variables were not significantly associated with work performance among fixed-night-shift nurses. Hierarchical multiple regression analysis showed that education level, job satisfaction and fixed-night-shift work were significant factors associated with work performance. The final model explained 17.0% of the variance in work performance, with an adjusted R2 of .15. Job satisfaction showed the strongest association.Conclusion: The relationship between sleep-related factors and work performance differed by work schedule type. These findings suggest that interventions to improve nurses’ work performance should combine sleep health management with organizational strategies, particularly efforts to improve job satisfaction. The role of fixed-night-shift nursing systems should be examined further in future studies.